Evaluation de l’hémogramme et la vitamine D chez la femme enceinte dans la localité de Mostaganem - Dekkiche, Fatiha; Bouziane, Fatiha (My University, 2020)
We studied the parameters of the blood count and the vitamin D level to determine the reference values in pregnant women, in the EHS Mother - Child Maternity of Lala kheira in Mostaganem city. We performed this study on 30 observations in pregnant women aged between 20 and 40 years old. Informed consent was obtained in all cases before inclusion in the study. The blood count parameters were studied on an automatic counter (Self-analyzer for FNS type Mythic 18), Normal clinical examination and a negative thick film were standard criteria, and vitamin D assay was performed by Roche Diagnostics® Cobas E 601 Test Analyzer . Of the 30 observations in pregnant women, the first trimester had 05(25%), 4 (20%) in the second trimester, 11 (5 5 %) in the third trimester and there are 3 observations in women enceinte for vitamin D, two subgroups of the 2nd and 3rd trimester. We observed during this study an increase in white blood cells and a decrease in red blood cells, hemoglobin, hematocrit , average blood volume and platelets with the age of pregnancy on the one hand in pregnant women and vitamin D level sin crease with gestational age. We found in our study that the values of the parameters of the blood count and the level of vitamin D as well in pregnant women we different from those of a population.
Keywords: Hemogram; Week of Amenorrhea; Vitamin D.